2023
DOI: 10.3390/foods12132499
|View full text |Cite
|
Sign up to set email alerts
|

Did the Addition of Olive Cakes Obtained by Different Methods of Oil Extraction in the Finishing Diet of Bísaro Pigs Affect the Volatile Compounds and Sensory Characteristics of Dry-Cured Loin and “Cachaço”?

Abstract: This study was conducted to determine the effects of different types of olive cake in the basal diet of Bísaro pigs on the volatile compounds and sensory characteristics of dry-cured loin and “cachaço”. A total of 40 Bísaro breed animals were allocated to four treatments, along with a control group (T1—control, T2—crude olive cake, T3—centrifugation two phases, T4—exhausted, and T5—exhausted with 1% of olive). Various extraction methods (centrifugation, pressing, and exhaustion) were employed for the olive cak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…The variability between all panellists was explained by the first two main factors (F1 and F2), which accounted for 54.6% of the total variation between samples. Although this value is lower than the 62.5% recorded by Leite et al [ 16 ] in the dry-cured loin of Bisaro pigs, it is still considered a good quality value. In total, five factors were required to explain 100% of the total variability ( Table 2 ).…”
Section: Resultscontrasting
confidence: 63%
“…The variability between all panellists was explained by the first two main factors (F1 and F2), which accounted for 54.6% of the total variation between samples. Although this value is lower than the 62.5% recorded by Leite et al [ 16 ] in the dry-cured loin of Bisaro pigs, it is still considered a good quality value. In total, five factors were required to explain 100% of the total variability ( Table 2 ).…”
Section: Resultscontrasting
confidence: 63%
“…Also, the flavor attribute is often perceived when the combination of odor (prior to consumption and retronasal olfaction) and taste perception, along with trigeminal perception, leads to flavor perception [43,44]. In addition, two odors that are likely to be detected in animals with a high live carcass weight and/or that are poorly castrated were analyzed: androsterone and scatol hormones of animal origin [45].…”
Section: Sensory Attributesmentioning
confidence: 99%
“…According to Domínguez et al [43], the reactions that release characteristic aromas (like hexanals) present a rancid aroma at high amounts, whereas at low amounts, it releases a pleasant grassy aroma. Odor is also an important attribute that interacts with flavor because the ripening degree (proteolysis and lipolysis changes that occur in the drying process) reflects the ripening odor compounds that become a significant part of the meat's flavor [45,51,52]. Also, Leite et al [45] found in their work with similar conditions for the production of cured Bísaro loins that specific ingredients in their formulation (for example, garlic) can be detected in this type of product.…”
Section: Sensory Datamentioning
confidence: 99%
See 2 more Smart Citations